2014
DOI: 10.3168/jds.2013-7251
|View full text |Cite
|
Sign up to set email alerts
|

Effect of method of delivery of sodium butyrate on maturation of the small intestine in newborn calves

Abstract: The effect of sodium butyrate (SB) supplementation in milk replacer (MR), starter mixture (SM), or both on small intestine maturation in newborn calves was investigated. Twenty-eight male calves with a mean age of 5 (± 1) d were randomly allocated into 1 of 4 groups (7 animals per group) and fed (1) MR and SM, without SB (MR(-) and SM(-), respectively; MR(-)/SM(-)); (2) MR(-) and SM supplemented with SB encapsulated within triglyceride matrix (SM(+), 0.6% as fed; MR(-)/SM(+)); (3) MR supplemented with crystall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
52
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 24 publications
8
52
0
Order By: Relevance
“…It has been shown that butyrate is an important regulator and stimulator for proliferation, differentiation, and apoptosis of epithelial cells in the stomach and small intestine of calves and piglets (Guilloteau et al, ; Kotunia et al, ; Mazzoni et al, ). Practically, Gorka et al () reported that sodium butyrate supplementation in MR increased ileum weight and length of newborn dairy calves. In the previous study, although total feed DMI and ME intake did not differ, supplementation of sodium butyrate in MR tended to increase BW at 7, 14, and 21 days after birth and ADG from 0 to 7 days after birth in newborn calves (Gorka et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that butyrate is an important regulator and stimulator for proliferation, differentiation, and apoptosis of epithelial cells in the stomach and small intestine of calves and piglets (Guilloteau et al, ; Kotunia et al, ; Mazzoni et al, ). Practically, Gorka et al () reported that sodium butyrate supplementation in MR increased ileum weight and length of newborn dairy calves. In the previous study, although total feed DMI and ME intake did not differ, supplementation of sodium butyrate in MR tended to increase BW at 7, 14, and 21 days after birth and ADG from 0 to 7 days after birth in newborn calves (Gorka et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, butyrate supplementation in diets may have positive effect on GIT development directly as well as indirectly through GLP‐2 action in calves. On the other hand, sodium butyrate supplementation in MR increased ileal length and tended to increase ileal weight in newborn calves whereas had no effect on plasma GLP‐2 concentration (Gorka et al, , ). As an alternative to sodium butyrate, glycerol tributyrate (tributyrin; TB) could be used as a butyrate source.…”
Section: Introductionmentioning
confidence: 99%
“…38 Sodium butyrate is involved in epithelial development in many species. It appears that adding it to milk replacer enhances intestinal development 39 while adding it to post-weaned heifer diets enhances feed efficiency. 40…”
Section: Sodium Butyratementioning
confidence: 99%
“…Although rumen development is often evaluated to assess weaning programs, it should be acknowledged that rumen development may be associated with developmental changes in the small intestine (Górka et al, 2011(Górka et al, , 2013 and thus, weaning may influence more regions than the rumen due to changes in nutrient supply and type of nutrient provided, as discussed above. Mannitol, inulin, and Cr-EDTA are markers that have been used to assess GIT permeability.…”
Section: Introductionmentioning
confidence: 98%